Dynamics of Change: Why Reactivity Matters. - MEDEIROS, ANDRE (Communications of the ACM, 2016)
The article discusses the challenges associated with managing change in a code base for computer programmers, focusing on the importance of reactivity. It looks at how change propagates from one module to another, passive programming, and reactive programming.